Trends in Survival After First Myocardial Infarction in People With Diabetes - Linn Glynn; Marcus Lind; Tomas Andersson; Björn Eliasson; Robin Hofmann; Thomas Nyström (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background The aim of this study was to investigate temporal trends in survival and subsequent cardiovascular events in a nationwide myocardial infarction population with and without diabetes. Methods and Results Between 2006 and 2020, we identified 2527 individuals with type 1 diabetes, 48 321 individuals with type 2 diabetes and 243 170 individuals without diabetes with first myocardial infarction in national health care registries. Outcomes were trends in all‐cause death after 30 and 365 days, cardiovascular death and major adverse cardiovascular events (ie, nonfatal stroke, nonfatal myocardial infarction, cardiovascular death, and heart failure hospitalization). Pseudo‐observations were used to estimate the mortality risk, with 95% CIs, using linear regression, adjusted for age and sex. Individuals with type 1 diabetes were younger (62±12.2 years) and more often women (43.6%) compared with individuals with type 2 diabetes (75±10.8 years; women, 38.1%), and individuals without diabetes (73±13.2 years; women, 38.4%). Early death decreased in people without diabetes from 23.1% to 17.5%, (annual change −0.48% [95% CI, −0.52% to −0.44%]) and in people with type 2 diabetes from 22.6% to 19.3% (annual change, −0.33% [95% CI, −0.43% to −0.24%]), with no such significant trend in people with type 1 diabetes from 23.8% to 21.7% (annual change, −0.18% [95% CI, −0.53% to 0.17%]). Similar trends were observed with regard to 1‐year death, cardiovascular death, and major adverse cardiovascular events. Conclusions During the past 15 years, the trend in survival and major adverse cardiovascular events in people with first myocardial infarction without diabetes and with type 2 diabetes have improved significantly. In contrast, a similar improvement was not seen in people with type 1 diabetes.